2012
DOI: 10.1016/j.cub.2012.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Imprint of Domestication on Genome Variation and Function of the Filamentous Fungus Aspergillus oryzae

Abstract: Summary The domestication of animals, plants and microbes fundamentally transformed the lifestyle and demography of the human species [1]. Although the genetic and functional underpinnings of animal and plant domestication are well understood, little is known about microbe domestication [2–6]. We systematically examined genome-wide sequence and functional variation between the domesticated fungus Aspergillus oryzae, whose saccharification abilities humans have harnessed for thousands of years to produce sake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
180
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 59 publications
16
180
0
1
Order By: Relevance
“…In our study, MALDI-TOF MS was shown to easily differentiate A. flavus and A. oryzae on the species level, and interestingly, clinical isolates of A. oryzae and A. flavus formed separate clusters with their corresponding reference strains, and both the clusters could be distinguished from those of A. parasiticus and A. alliaceus, respectively [35]. Although A. flavus produces harmful aflatoxins while A. oryzae does not, nonaflatoxigenic isolates of A. flavus are highly related to A. oryzae, and this is consistent with the hypothesis that an atoxigenic lineage of A. flavus has gradually evolved into a domesticated A. oryzae through selection by humans [36]. As several non(afla)toxigenic A. flavus isolates are phenotypically more similar to A. oryzae than to other A. flavus isolates, a molecular-phenotypic approach such as MALDI-TOF MS could be very useful for discriminating toxigenic from atoxigenic strains within the A. flavus species [24].…”
Section: Closely Related Species Differentiationsupporting
confidence: 81%
“…In our study, MALDI-TOF MS was shown to easily differentiate A. flavus and A. oryzae on the species level, and interestingly, clinical isolates of A. oryzae and A. flavus formed separate clusters with their corresponding reference strains, and both the clusters could be distinguished from those of A. parasiticus and A. alliaceus, respectively [35]. Although A. flavus produces harmful aflatoxins while A. oryzae does not, nonaflatoxigenic isolates of A. flavus are highly related to A. oryzae, and this is consistent with the hypothesis that an atoxigenic lineage of A. flavus has gradually evolved into a domesticated A. oryzae through selection by humans [36]. As several non(afla)toxigenic A. flavus isolates are phenotypically more similar to A. oryzae than to other A. flavus isolates, a molecular-phenotypic approach such as MALDI-TOF MS could be very useful for discriminating toxigenic from atoxigenic strains within the A. flavus species [24].…”
Section: Closely Related Species Differentiationsupporting
confidence: 81%
“…We have shown that A. oryzae DAR3699 has a mutation in the promoter of its creB gene; that it has many phenotypes consistent with loss of creB function, including strong growth on acet- amide, weak growth on proline, quinate, or arabinose, resistance to molybdate, high protease secretion, and little or no inhibition of spore germination by glucose; and that deleting creB in this strain does not change the phenotype. A. oryzae arose through the ancient domestication of Aspergillus flavus and has undergone genetic changes during its centuries of use in Asian food and beverage production (29). Our data suggest that for A. oryzae DAR3699, one of these genetic changes is likely to have been partial or complete loss of creB function.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, this powerful technique arises as an efficient tool for transcriptomic analyses in the genus Aspergillus, as shown in 2010 by Wang and coworkers (11), who published the first RNA-seq-based transcriptomic study of this genus. In these last 2 years, the RNA-seq-based studies involving Aspergillus species analyzed the temperature effect on secondary metabolite synthesis, biofilm formation, the response to lignocellulose, or domestication in A. fumigatus, A. flavus, A. niger, or A. oryzae, respectively (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%